ChemInform Abstract: Direct Substitution of Primary Allylic Amines with Sulfinate Salts. Issue 9 (5th March 2013) - Wu, Xue‐Song; Chen, Yan; Li, Man‐Bo; Zhou, Meng‐Guang; Tian, Shi‐Kai
Abstract The process is applied to a broad spectrum of substrates where high regioselectivity is observed.